Digital Currencies and Monetary Policy Effectiveness: What Does the Data Say? - Adenutsi, Deodat Emilson (International Journal of Economics and Financial Issues, 2025)
This study investigates the impact of digital currencies (including central bank digital currencies [CBDCs], cryptocurrencies, and Ethereum) on monetary policy effectiveness, specifically focusing on inflation-targeting success and financial stability. Using Autoregressive Distributed Lag (ARDL) modelling on monthly global data spanning January 2010 to December 2024, the empirical findings demonstrate that digital currencies significantly improve monetary policy outcomes. The results indicate that CBDCs and Ethereum transactions notably enhance inflation-targeting success, enabling central banks to better achieve targeted inflation through improved transaction efficiency and transparency. Ethereum also consistently demonstrates a stabilising impact on financial stability by reducing inflation volatility. Conversely, cryptocurrencies exhibit mixed impacts, suggesting potential speculative disruptions. The error-correction mechanisms highlight robust short-run adjustments towards equilibrium, supporting the reliability of the ARDL approach. These findings emphasize the need for policymakers to strategically integrate digital currencies into monetary policy frameworks, and recommend enhanced regulatory oversight, strategic adoption of Ethereum technology, and careful management of monetary growth and velocity of money to sustain economic stability.